Terahertz generation via the inverse orbital Rashba-Edelstein effect at the Ni/CuO_{x} interface - Renyou Xu; Xiaobai Ning; Houyi Cheng; Yuxuan Yao; Zejun Ren; Shaojie Liu; Mingcong Dai; Yong Xu; Sai Li; Ao Du; Xiaojun Wu; Fengxia Hu; et al. (Physical Review Research)
Orbitronics provides novel mechanisms to generate terahertz (THz) emission using the orbital angular momentum of electrons. Here, we report a systematic investigation of the THz emission from Ni/CuO_{x} heterostructures pumped by a femtosecond laser pulse. Despite the very weak spin-orbit coupling of CuO_{x}, considerable THz radiation from Ni/CuO_{x} has been observed, with a polarity state that is magnetically controllable and the intensity as much as about 20% of that found in Ni/Pt spintronic THz emitter. We find conclusive evidence that THz radiation stems from the inverse orbital Rashba-Edelstein effect at the Ni/CuO_{x} interface, which can be manipulated by tuning oxygen-induced orbital hybridization. Our experimental results of Ni thickness-dependent THz emission, combined with theoretical modeling, reveal long-range diffusion-length characteristics of orbital current within the Ni layer. This work enhances the understanding of the THz emission mechanism based on orbital-to-charge conversion, providing guidance for the development of orbitronic THz emitters.